Method for measuring carbonization reaction degree of calcium silicate and calcium-silicon ratio in silica gel
The chemical state of silicon elements in calcium silicate carbide products is measured by solid nuclear magnetic silicon spectroscopy, the degree of carbonization reaction is calculated, and the calcium-silicon ratio in silicon gel is measured in combination with the carbon fixation method, which solves the problem of large measurement errors in the prior art and improves the measurement accuracy.
Patent Information
- Application Number
- CN202411741868.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-14
AI Technical Summary
In the prior art, the reaction degree of calcium silicate in carbon-fixed gelling materials is difficult to accurately measure, and the measurement error of the calcium-silicon ratio in silica gel is relatively large, which affects the judgment of reaction activity and rate.
Solid nuclear magnetic silicon spectroscopy was used to measure the chemical state of silicon elements in calcium silicate carbide products, the degree of carbonization reaction of calcium silicate was calculated by the proportion of silicon elements participating in the reaction to all silicon elements, and the calcium-silicon ratio in silicon gel was calculated by combining the carbon sequestration method.
The measurement accuracy of the degree of calcium silicate carbonization reaction is improved, and the calcium-silicon ratio in silicone is accurately reflected, and the problem of large measurement errors in the prior art is solved.
Smart Images

Figure CN119619210A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a method for measuring the carbonization reaction degree of calcium silicate and the calcium-silicon ratio in silica gel. Background Art
[0002] In recent years, the carbon emissions from the construction industry have increased year by year. Among them, the main sources of carbon emissions from the cement industry include fuel combustion, limestone decomposition, and grinding power consumption. In order to achieve carbon dioxide emission reduction in the cement industry, carbon-fixing cementitious materials came into being. Carbon-fixing cementitious materials refer to low-carbon cementitious materials that can spontaneously and quickly react with CO2 gas at room temperature and pressure, and can cement other materials into a whole with high mechanical strength. Carbon-fixing cementitious materials mainly include clinker mainly composed of low-calcium non-hydraulic calcium silicate mineral phases such as γ-C2S, C3S2 and CS, and industrial solid waste rich in calcium silicate mineral phases.
[0003] However, there are some problems in the current research on carbon-fixing cementitious materials. For example, the reaction degree of the main mineral phase (calcium silicate) in carbon-fixing cementitious materials is difficult to determine. At present, the reaction degree is indirectly reflected by measuring the amount of calcium carbonate generated during the reaction of calcium silicate (hereinafter referred to as the carbon fixation method). However, during the reaction of calcium silicate, some calcium ions combine with carbonate ions to generate calcium carbonate, while the other part of calcium ions enter the silica gel. Therefore, the carbonization degree calculated based on the carbon fixation method ignores the calcium ions entering the silica gel, which makes the calculated carbonization degree and the reaction degree have a large deviation. This makes it difficult to accurately judge the reaction activity and reaction rate of carbon-fixing cementitious materials, thereby limiting the research and application of carbon-fixing cementitious materials. In addition, as one of the main carbonization products of calcium silicate, the composition of silica gel has always been difficult to measure accurately. At present, the calcium-silicon ratio of silica gel can only be measured by EDS, and the test data of EDS has large errors, and the calcium-silicon ratio of local silica gel can only be measured at the microscopic scale.
[0004] Therefore, there is an urgent need to provide a new method for measuring the carbonization reaction degree of calcium silicate and the calcium-silicon ratio in silica gel to solve the above problems. Summary of the invention
[0005] The purpose of the present invention is to overcome the above-mentioned technical deficiencies and propose a method for measuring the carbonization reaction degree of calcium silicate and the calcium-silicon ratio in silica gel, so as to solve the technical problems in the prior art of inaccurate carbonization degree measurement based on the carbon fixation method and large error of the calcium-silicon ratio in silica gel measured based on EDS.
[0006] In a first aspect, the present invention provides a method for measuring the degree of carbonization reaction of calcium silicate, comprising the following steps: S1. Obtaining a calcium silicate carbonized product; S2. Obtain a solid nuclear magnetic resonance silicon spectrum of the calcium silicate carbonized product, and obtain the silicon element content information participating in the reaction and all silicon element content information in the calcium silicate carbonized product based on the solid nuclear magnetic resonance silicon spectrum; S3. Determine the carbonization reaction degree of the calcium silicate based on the silicon content information participating in the reaction and the total silicon content information in the calcium silicate carbonization product.
[0007] In a second aspect, the present invention provides a method for measuring the calcium-silicon ratio in silica gel, comprising the following steps: M1. Determine the carbonization degree of calcium silicate according to the carbon fixation amount of calcium silicate carbonized products; M2. Construct a first theoretical relationship model of the calcium-silicon ratio in silica gel, and determine the calcium-silicon ratio in silica gel based on the carbonization reaction degree of calcium silicate, the carbonization degree and the first theoretical relationship model; wherein the calculation formula corresponding to the first theoretical relationship model is: y=x(ab) / a(1) Compared with the prior art, the beneficial effects of the present invention include: The present invention quantitatively calculates the ratio of silicon elements participating in the reaction in calcium silicate to all silicon elements by solid nuclear magnetic silicon spectrum to obtain the carbonization reaction degree of calcium silicate, and calculates the calcium-silicon ratio of silica gel in combination with the carbonization degree obtained by the carbon fixation method, thereby solving the problem of partial calcium ions entering silica gel that was previously ignored by the carbon fixation method. The accuracy of the method for measuring the carbonization reaction degree of calcium silicate of the present invention is significantly higher than the carbonization degree measured by the carbon fixation method, and the accuracy of the method for measuring the calcium-silicon ratio in silica gel is significantly higher than the energy spectrum, providing a new idea for determining the reaction degree of calcium silicate and the calcium-silicon ratio in silica gel. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] Figure 1 It is a process flow chart of an embodiment of a method for measuring the degree of carbonization reaction of calcium silicate provided by the present invention; Figure 2 It is a schematic diagram corresponding to the chemical environment in which Si may exist in calcium silicate carbide products; Figure 3 It is a process flow chart of an embodiment of a method for measuring the calcium-silicon ratio in silica gel provided by the present invention; Figure 4 is the γ-C2S carbonized product in Example 1 of the present invention 29 Si MAS NMR spectrum; Figure 5 is the β-C2S carbonized product in Example 2 of the present invention 29 Si MAS NMR spectrum; Figure 6 is the C3S carbonized product in Example 3 of the present invention 29 Si MAS NMR spectrum; Figure 7is the carbonized product of C3S2 in Example 4 of the present invention 29 Si MAS NMR spectrum; Figure 8 The carbonized β-C2S products in Example 2 and Comparative Example 1 are 29 Si MAS NMR spectrum. DETAILED DESCRIPTION
[0009] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0010] At present, those skilled in the art generally believe that the reaction degree of calcium silicate cannot be calculated, because during the carbonization reaction of calcium silicate, the calcium element has two destinations: it can enter calcium carbonate and it can enter silica gel. Since the calcium content in silica gel is difficult to determine, it is impossible to calculate the calcium content involved in the reaction, resulting in the inability to calculate the reaction degree. The inventors took into account that the silicon element has only one destination during the reaction of calcium silicate: forming silica gel. Therefore, the present invention uses solid nuclear magnetic silicon spectrum to accurately quantify the silicon element in silica gel and calcium silicate, and accurately calculates the carbonization reaction degree of calcium silicate by the ratio of the silicon element participating in the reaction to all silicon elements in the sample, and creatively proposes a method for measuring the carbonization reaction degree of calcium silicate based on solid nuclear magnetic silicon spectrum.
[0011] Furthermore, by comparing the carbonization degree obtained by the above method with the carbonization degree obtained by the carbon fixation method, it can be found that the carbonization degree of calcium silicate is significantly higher than the carbonization degree. This is because the carbonization degree only measures the calcium that enters the calcium carbonate, while the other part of the calcium that enters the silica gel is not measured. Therefore, the calcium content in the silica gel can be obtained based on the difference between the carbonization degree and the carbonization degree of calcium silicate, and the calcium-silicon ratio of the silica gel is finally calculated by combining the silicon content in the silica gel calculated by solid nuclear magnetic resonance silicon spectrum. Unlike EDS measurement, this method can accurately reflect the calcium-silicon ratio of the silica gel in the whole sample. Taking C3S2 as an example, assuming that there is 1 mol of C3S2 before the carbonization reaction, the carbonization degree is a, and the carbonization degree is b, then 3a mol of calcium participates in the reaction and 3b mol of calcium carbonate is generated. Therefore, there are 3 (ab) mol of calcium in the silica gel. According to the carbonization reaction degree a, there are 2a mol of silicon in the silica gel. Therefore, the calcium-silicon ratio in the silica gel is 3 (ab) / 2a. Taking C3S2 as an example, the reaction formula is as follows: x(3CaO·2SiO2)+yCO2+nH2O→yCaCO3+(3x-y)CaO·2xSiO2·nH2O Based on this, the present invention is proposed.
[0012] See also Figure 1 In a first aspect, the present invention provides a method for measuring the degree of carbonization reaction of calcium silicate, comprising the following steps: S1. Obtaining a calcium silicate carbonized product; S2. Obtain a solid nuclear magnetic resonance silicon spectrum of the calcium silicate carbonized product, and obtain the silicon element content information participating in the reaction and all silicon element content information in the calcium silicate carbonized product based on the solid nuclear magnetic resonance silicon spectrum; S3. Determine the carbonization reaction degree of the calcium silicate based on the silicon content information participating in the reaction and the total silicon content information in the calcium silicate carbonization product.
[0013] The present invention tests the chemical state of silicon in the calcium silicate carbonized product by using solid nuclear magnetic silicon spectrum, and determines the carbonization reaction degree of calcium silicate and the calcium-silicon ratio in silica gel based on the chemical state of silicon. The present invention can effectively solve the problems that the existing carbonization degree test can only monitor the amount of calcium carbonate generated but cannot monitor the amount of calcium ion generated in silica gel, resulting in difficulty in measuring the reaction degree, and the problem that the calcium-silicon ratio test data in silica gel based on EDS has large errors and it is difficult to obtain the calcium-silicon ratio of silica gel in the whole sample. The carbonization reaction degree and the calcium-silicon ratio in silica gel measured by the present invention are more accurate.
[0014] In this embodiment, in step S1, the calcium silicate carbonized product is obtained by subjecting the carbon-fixing cementitious material to a carbonization reaction. The present invention has no limitation on the water-solid ratio before carbonization, the molding method, the curing time during the carbonization process, and the carbon dioxide concentration. Those skilled in the art can select any water-solid ratio, molding method, curing time, and carbon dioxide concentration according to actual conditions.
[0015] The carbon-fixing cementitious material is a single calcium silicate mineral with a purity of ≥90%, and the single calcium silicate mineral is one of C3S, β-C2S, γ-C2S, C3S2, and CS.
[0016] In this embodiment, in step S1, the particle size of the calcium silicate carbonized product is ≤75 μm. If the particle size of the calcium silicate carbonized product is too large, it will cause uneven distribution of the sample during the solid nuclear magnetic resonance measurement process, and the measurement data will be inaccurate.
[0017] In some specific embodiments of the present invention, the calcium silicate carbonized product is obtained by grinding the carbon-fixing cementitious material to less than 75 μm after carbonization reaction.
[0018] In this embodiment, in step S2, the content information of silicon elements participating in the reaction in the calcium silicate carbonized product includes the peak area of silicon elements participating in the reaction in the calcium silicate carbonized product, and the content information of all silicon elements in the calcium silicate carbonized product includes the peak area of all silicon elements in the calcium silicate carbonized product.
[0019] In this implementation, step S2 includes: S21, performing solid nuclear magnetic resonance silicon spectrum testing on the calcium silicate carbonized product to obtain a solid nuclear magnetic resonance silicon spectrum; S22, performing peak fitting on the solid NMR silicon spectrum to obtain the peak area of silicon element under different chemical environments; S23. Determine the peak area of the silicon element participating in the reaction and the peak areas of all silicon elements based on the peak areas of the silicon element under different chemical environments.
[0020] See also Figure 2 The chemical environment of Si is usually represented by Q n Indicates, where n represents the number of bridging oxygens, which means that two ends of an oxygen atom are connected to two silicon-oxygen tetrahedrons. The calcium silicate mineral Q is marked in the figure. n The specific structure of the structural unit.
[0021] Wherein, in step S21, the main mineral phases of the carbon-fixing cementitious material are C3S, γ-C2S, C3S2, and CS. During the solid-state nuclear magnetic resonance test, the relaxation time is ≥8s, further 8-12s, further 10s, and the number of scans is ≥540 frames, further 540-560 frames, and further 550 frames. If the relaxation time is too short, the measurement data will be inaccurate. If the relaxation time is too long, the test cost will increase. If the number of scans is too small, the signal-to-noise ratio of the test data will be too low, and the test data will be inaccurate; if the number of scans is too large, the test cost will increase.
[0022] Wherein, in step S21, the main mineral phase of the carbon-fixing cementitious material is β-C2S, and during the solid-state nuclear magnetic resonance test, the relaxation time is ≥590s, further 590-610s, further 600s, and the number of scans is ≥30 frames, further 30-34 frames, and further 32 frames. If the relaxation time is too short, the measurement data will be inaccurate, and if the relaxation time is too long, the test cost will increase. If the number of scans is too small, the signal-to-noise ratio of the test data will be too low, and the test data will be inaccurate; if the number of scans is too large, the test cost will increase.
[0023] The present invention does not specifically limit the software used for peak fitting of solid NMR silicon spectrum, and those skilled in the art can select the software according to actual conditions, as long as the software can accurately fit the solid NMR silicon spectrum.
[0024] In this embodiment, step S3 includes: determining the degree of carbonization reaction of calcium silicate according to the ratio of the sum of the peak areas of silicon elements participating in the reaction to the peak areas of all silicon elements in the calcium silicate carbonized product.
[0025] Among them, the main mineral phases of carbon-fixing cementitious materials are C3S, β-C2S or γ-C2S, and the chemical environment of Si before the reaction is only Q 0This is because the silicon-oxygen tetrahedrons in the C3S, β-C2S and γ-C2S crystal structures are not connected, so the chemical environment of Si before the reaction only has Q 0 structure, the reaction may increase Q 1 , Q 2 , Q 3 , Q 4 , so the calculation formula for the carbonization reaction degree of calcium silicate is: a=(S Q1 +S Q2 +S Q3 +S Q4 ) / (S Q0 +S Q1 +S Q2 +S Q3 +S Q4 ); It should be noted that when the main mineral phase of the carbon-fixing cementitious material is γ-C2S, due to its low hydration activity, no hydration reaction will occur during the carbonization process to generate Q1 and Q2 structures (CSH). After the reaction, only Q 3 , Q 4 Structure (silica gel), i.e. S Q1 and S Q2 Both are 0, so the calculation formula for the carbonization reaction degree of calcium silicate can be simplified as: a=(S Q3 +S Q4 ) / (S Q0 +S Q3 +S Q4 ); Among them, the main mineral phase of carbon-fixing cementitious materials is C3S2, and the chemical environment of Si before the reaction is only Q 1 This is because there are two silicon-oxygen tetrahedrons connected in the C3S2 crystal structure, so Q exists before the reaction. 1 Structure. Due to the low hydration activity during the carbonization reaction, no hydration reaction will occur during the carbonization process to generate Q1 and Q2 structures (CSH), so only Q is increased after the reaction. 3 , Q 4 structure (silica gel), so the calculation formula for the carbonization reaction degree of calcium silicate is: a=(S Q3 +S Q4 ) / (S Q1 +S Q3 +S Q4 ); Among them, the main mineral phase of carbon-fixing cementitious materials is CS, and the chemical environment of Si before the reaction is only Q 2 This is because the silicon-oxygen tetrahedrons in the CS crystal are connected in a ring shape, so before the reaction, Q 2The structure exists. Due to the low hydration activity during the carbonization reaction, no hydration reaction will occur during the carbonization process to generate Q1 and Q2 structures (CSH), so only Q is increased after the reaction. 3 , Q 4 structure (silica gel), so the calculation formula for the carbonization reaction degree of calcium silicate is: a=(S Q3 +S Q4 ) / (S Q2 +S Q3 +S Q4 ); In the formula, S Q0 , S Q1 , S Q2 , S Q3 and S Q4 They are respectively Q 0 , Q 1 , Q 2 , Q 3 and Q 4 The corresponding peak area.
[0026] See also Figure 3 In a second aspect, the present invention provides a method for measuring the calcium-silicon ratio in silica gel, comprising the following steps: M1. Determine the carbonization degree of calcium silicate according to the carbon fixation amount of calcium silicate carbonized products; M2. Construct a first theoretical relationship model of the calcium-silicon ratio in silica gel, and determine the calcium-silicon ratio in silica gel based on the carbonization reaction degree of calcium silicate, the carbonization degree and the first theoretical relationship model; wherein the calculation formula corresponding to the first theoretical relationship model is: y=x(ab) / a(1) In formula (1), a is the degree of carbonization reaction, b is the degree of carbonization, x is the calcium-silicon ratio of calcium silicate, and y is the calcium-silicon ratio of silica gel.
[0027] In this implementation, step M1 includes: M11. Obtain the ignition loss of calcium silicate carbonized products; M12. Construct a second theoretical relationship model between the carbonization degree and ignition loss of calcium silicate, and determine the carbonization degree of calcium silicate based on the second theoretical relationship model.
[0028] The ignition loss of calcium silicate carbonized products is the ignition loss of calcium silicate carbonized products at 300℃-1000℃, and the heating rate is ≤10℃ / min. If the heating rate is too high, the calcium carbonate in the calcium silicate carbonized products will not be fully decomposed, and the calculation results will be inaccurate.
[0029] Among them, the formula corresponding to the second theoretical relationship model is: (2) In formula (2), b is the carbonization degree, x is the calcium-silicon ratio of calcium silicate, and m is 300 is the mass of the carbonized product when the calcination temperature rises to 300°C, m 1000 It is the mass of the carbonized product when the calcination temperature rises to 1000℃.
[0030] Example 1 (Raw material: γ-C2S) The composition of calcium silicate carbonized products before carbonization is: γ-C2S accounts for 95%; calcium silicate is mixed with water, the water-solid ratio is 0.15, and the green body is obtained by pressing, and the molding pressure is 30MPa. Then, carbon dioxide curing is carried out at a pressure of 0.2MPa, the carbon dioxide concentration is 99%, and the curing time is 24h.
[0031] The method for measuring the carbonization reaction degree of calcium silicate and the calcium-silicon ratio in silica gel provided in this embodiment comprises the following steps: (1) The calcium silicate carbide product was ground to less than 75 μm and then subjected to solid-state NMR silicon spectrum testing with a relaxation time of 10 s and a scanning number of 550 frames; (2) The software was used to perform peak fitting on the solid NMR spectrum of calcium silicate carbonized products to obtain the different chemical environments (Q 0 , Q 1 , Q 2 , Q 3 , Q 4 ) The peak area of silicon element under (3) The carbonization reaction degree of calcium silicate is calculated by taking the ratio of the sum of the peak areas of silicon participating in the reaction to the area ratio of all peaks in the spectrum (S Q3 +S Q4 ) / (S Q0 +S Q3 +S Q4 ) = (49.1% + 26.2%) / (24.7% + 49.1% + 26.2%) = 75.3%, recorded as a; (4) Test the ignition loss of calcium silicate carbonized products at 300℃-1000℃, with a heating rate of 5℃ / min, and measure m 300 =10.8g, m 1000 = 8.5g, calculate the carbonization degree as .
[0032] (5) Based on the carbonization reaction degree a and carbonization degree b of calcium silicate, the calculated calcium-silicon ratio in silica gel is y=2(ab) / a=2×(75.3%-52.9%) / 75.3%=0.59.
[0033] Example 2 (Raw material is β-C2S) The composition of the calcium silicate carbonized product before carbonization is: β-C2S accounts for 95%, and its preparation method and process parameters are consistent with those in Example 1.
[0034] The method for measuring the carbonization reaction degree of calcium silicate and the calcium-silicon ratio in silica gel provided in this embodiment comprises the following steps: (1) The calcium silicate carbide product was ground to less than 75 μm and then subjected to solid-state NMR silicon spectrum testing with a relaxation time of 600 s and a scanning number of 32 frames; (2) The software was used to perform peak fitting on the solid NMR spectrum of calcium silicate carbonized products to obtain the different chemical environments (Q 0 , Q 1 , Q 2 , Q 3 , Q 4 ) The peak area of silicon element under (3) The carbonization reaction degree of calcium silicate is calculated by the ratio of the sum of the peak areas of silicon participating in the reaction to the area of all peaks in the spectrum (S Q1 +S Q2 +S Q3 +S Q4 ) / (S Q0 +S Q1 +S Q2 +S Q3 +S Q4 ) = (0% + 0% + 29.1% + 23.2%) / (47.7% + 0% + 0% + 29.1% + 23.2%) = 52.3%, recorded as a; (4) Test the ignition loss of calcium silicate carbonized products at 300℃-1000℃, with a heating rate of 5℃ / min. The calculated carbonization degree is ; (5) Based on the carbonization reaction degree a and carbonization degree b of calcium silicate, the calculated calcium-silicon ratio in silica gel is y=2(ab) / a=2×(52.3%-34.6%) / 52.3%=0.68.
[0035] Example 3 (Raw material: C3S) The composition of the calcium silicate carbonized product before carbonization is: C3S accounts for 92%, and its preparation method and process parameters are consistent with those in Example 1.
[0036] The method for measuring the carbonization reaction degree of calcium silicate and the calcium-silicon ratio in silica gel provided in this embodiment comprises the following steps: (1) The calcium silicate carbide product was ground to less than 75 μm and then subjected to solid-state NMR silicon spectrum testing with a relaxation time of 10 s and a scanning number of 550 frames; (2) The software was used to perform peak fitting on the solid NMR spectrum of calcium silicate carbonized products to obtain the different chemical environments (Q0 , Q 1 , Q 2 , Q 3 , Q 4 ) The peak area of silicon element under (3) The carbonization reaction degree of calcium silicate is calculated by the ratio of the sum of the peak areas of silicon participating in the reaction to the area of all peaks in the spectrum (S Q1 +S Q2 +S Q3 +S Q4 ) / (S Q0 +S Q1 +S Q2 +S Q3 +S Q4 ) = (16.1% + 23.2% + 0% + 0%) / (60.7% + 16.1% + 23.2% + 0% + 0%) = 39.3%, recorded as a; (4) Test the ignition loss of calcium silicate carbonized products at 300℃-1000℃, with a heating rate of 5℃ / min, and calculate the degree of carbonization: ; (5) Based on the carbonization reaction degree a and carbonization degree b of calcium silicate, the calculated calcium-silicon ratio in silica gel is y=3(ab) / a=3×(39.3%-24.4%) / 39.3%=1.14.
[0037] Example 4 (Raw material: C3S2) The components of the calcium silicate carbonized product before carbonization are: C3S2 accounts for 93%, and its preparation method and process parameters are consistent with those of Example 1, and the carbonization curing time is 12h.
[0038] The method for measuring the carbonization reaction degree of calcium silicate and the calcium-silicon ratio in silica gel provided in this embodiment comprises the following steps: (1) The calcium silicate carbide product was ground to less than 75 μm and then subjected to solid-state NMR silicon spectrum testing with a relaxation time of 10 s and a scanning number of 550 frames.
[0039] (2) The software was used to perform peak fitting on the solid NMR spectrum of calcium silicate carbonized products to obtain the different chemical environments (Q 0 , Q 1 , Q 2 , Q 3 , Q 4 ) The peak area of silicon element under (3) The carbonization reaction degree of calcium silicate is calculated by the ratio of the sum of the peak areas of silicon participating in the reaction to the area of all peaks in the spectrum (S Q3 +S Q4 ) / (S Q1 + S Q3 +SQ4 )=(23.4%+28.1%) / (48.5%+23.4%+28.1%)=51.5%, recorded as a.
[0040] (4) Test the ignition loss of calcium silicate carbonized products at 300℃-1000℃, with a heating rate of 5℃ / min. The calculated carbonization degree is .
[0041] (5) According to the carbonization reaction degree a and carbonization degree b of calcium silicate, the calculated calcium-silicon ratio in silica gel is y=1.5*(ab) / a=1.5×(51.5%-28.6%) / 51.5%=0.67.
[0042] Comparative Example 1 (β-C2S relaxation time is too short) Compared with Example 2, the only difference is that during the test of solid-state nuclear magnetic spectrum, the relaxation time is 10 s and the scanning number is 550 frames.
[0043] Comparative Example 2 Compared with Example 4, the only difference is that EDS is used to test the calcium-silicon ratio of silica gel in the calcium silicate carbonized product.
[0044] Performance Testing The test results of the above embodiments and comparative examples are shown in Tables 1 and Figure 4-8 shown.
[0045] Table 1 Calculation results of carbonization reaction degree, carbonization degree, and calcium-silicon ratio calculated for the examples and comparative examples
[0046] See also Figure 4-7 and Table 1, by Figure 4-7 It can be seen from Table 1 that the carbonization reaction degree a of calcium silicate determined by the method of the present invention is greater than the reaction degree b, indicating that the carbonization reaction degree of calcium silicate calculated by the method of the present invention is more accurate. The accuracy of the calcium-silicon ratio in silica gel obtained by combining it with the reaction degree calculated by the carbon fixation method is significantly higher than that of the energy spectrum.
[0047] See also Figure 8 ,pass Figure 8 It can be seen that when the relaxation time is 10s, Q 0 The area of Q is much smaller than that of Q when the relaxation time is 600s. 0 The reason is that the relaxation time is not enough, Q 0 The signal is not fully collected, making Q 0 The smaller area ultimately results in a decrease in the degree of reaction and the accuracy of the silica gel-calcium-silicon ratio.
[0048] Please refer to Table 1. It can be seen from Table 1 that the calcium-silicon ratio of silica gel measured by EDS is 0.2~0.9. The data fluctuation range is obviously larger, and it is difficult to accurately determine the calcium-silicon ratio of silica gel.
[0049] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for measuring the degree of carbonization reaction of calcium silicate, characterized in that: The following steps are involved: S1. Obtaining a calcium silicate carbonized product; S2. Obtaining a solid nuclear magnetic resonance silicon spectrum of the calcium silicate carbonized product, and obtaining information on the content of silicon elements involved in the reaction and information on the content of all silicon elements in the calcium silicate carbonized product based on the solid nuclear magnetic resonance silicon spectrum; S3. Determine the carbonization reaction degree of the calcium silicate based on the silicon content information participating in the reaction and all silicon content information in the calcium silicate carbonized product.
2. The method for measuring the degree of carbonization reaction of calcium silicate according to claim 1, characterized in that: In step S1, the calcium silicate carbonized product is obtained by subjecting a carbon-fixing cementitious material to a carbonization reaction; wherein: The carbon-fixing cementitious material is a single calcium silicate mineral with a purity of ≥90%, and the single calcium silicate mineral is one of C3S, β-C2S, γ-C2S, C3S2, and CS; The particle size of the calcium silicate carbonized product is ≤75 μm.
3. The method for measuring the degree of carbonization reaction of calcium silicate according to claim 1, characterized in that: In step S1, the content information of silicon element participating in the reaction in the calcium silicate carbonized product includes the peak area of silicon element participating in the reaction in the calcium silicate carbonized product, and the content information of all silicon elements in the calcium silicate carbonized product includes the peak area of all silicon elements in the calcium silicate carbonized product.
4. The method for measuring the degree of carbonization reaction of calcium silicate according to claim 1, characterized in that: Step S2 includes: S21, performing a solid nuclear magnetic resonance silicon spectrum test on the calcium silicate carbonized product to obtain a solid nuclear magnetic resonance silicon spectrum; S22, performing peak fitting on the solid nuclear magnetic resonance silicon spectrum to obtain the peak areas of silicon elements under different chemical environments; S23, determining the peak area of the silicon element participating in the reaction and the peak area of all silicon elements based on the peak area of the silicon element under the different chemical environments; Among them, the chemical environment of Si is usually represented by Q n Indicates, where n represents the number of bridging oxygens, and bridging oxygen means that two silicon-oxygen tetrahedrons are connected at both ends of an oxygen atom.
5. The method for measuring the degree of carbonization reaction of calcium silicate according to claim 4, characterized in that: In step S21, the main mineral phase of the carbon-fixing cementitious material is one of C3S, γ-C2S, C3S2, and CS, and during the solid-state nuclear magnetic resonance test, the relaxation time is ≥8s and the number of scans is ≥540 frames; or, The main mineral phase of the carbon-fixing cementitious material is β-C2S. During the solid-state nuclear magnetic resonance test, the relaxation time is ≥590s and the scanning times are ≥30 frames.
6. The method for measuring the degree of carbonization reaction of calcium silicate according to claim 1, characterized in that: Step S3 includes: determining the carbonization reaction degree of the calcium silicate according to the ratio of the sum of the peak areas of silicon elements participating in the reaction in the calcium silicate carbonized product to the peak areas of all silicon elements.
7. The method for measuring the degree of carbonization reaction of calcium silicate according to claim 6, characterized in that: The main mineral phase of the carbon-fixing cementitious material is one of C3S, β-C2S, and γ-C2S. The calculation formula for the carbonization reaction degree of the calcium silicate is: a = (S Q1 + S Q2 + S Q3 + S Q4 ) / (S Q0 + S Q1 + S Q2 + S Q3 + S Q4 ); or, The main mineral phase of the carbon-fixing cementitious material is C3S2, and the calculation formula for the carbonization reaction degree of the calcium silicate is: a=(S Q3 +S Q4 ) / (S Q1 +S Q3 +S Q4 );or, The main mineral phase of the carbon-fixing cementitious material is CS, and the calculation formula for the carbonization reaction degree of the calcium silicate is: a=(S Q3 +S Q4 ) / (S Q2 +S Q3 +S Q4 ); In the formula, S Q0 , S Q1 , S Q2 , S Q3 and S Q4 They are respectively Q 0 , Q 1 , Q 2 , Q 3 and Q 4 The corresponding peak area.
8. A method for measuring the calcium-silicon ratio in silica gel, characterized in that: The following steps are involved: M1. Determine the carbonization degree of calcium silicate according to the carbon fixation amount of calcium silicate carbonized products; M2. Constructing a first theoretical relationship model of the calcium-silicon ratio in silica gel, and determining the calcium-silicon ratio in silica gel based on the carbonization reaction degree of the calcium silicate, the carbonization degree and the first theoretical relationship model; wherein, The calculation formula corresponding to the first theoretical relationship model is: y=x(ab) / a(1) In formula (1), a is the degree of carbonization reaction, which is obtained by the method for measuring the degree of carbonization reaction of calcium silicate according to any one of claims 1 to 7; b is the degree of carbonization, x is the calcium-silicon ratio of calcium silicate, and y is the calcium-silicon ratio of silica gel.
9. The method for measuring the calcium-silicon ratio in silica gel according to claim 8, characterized in that: Step M1 includes: M11. Obtain the ignition loss of calcium silicate carbonized products; M12. Constructing a second theoretical relationship model between the carbonization degree and the ignition loss of the calcium silicate, and determining the carbonization degree of the calcium silicate based on the second theoretical relationship model; wherein, The formula corresponding to the second theoretical relationship model is: (2) In formula (2), b is the carbonization degree, x is the calcium-silicon ratio of calcium silicate, and m is 300 is the mass of the carbonized product when the calcination temperature rises to 300°C, m 1000 It is the mass of the carbonized product when the calcination temperature rises to 1000℃.
10. The method for measuring the calcium-silicon ratio in silica gel according to claim 8, characterized in that: The ignition loss of the calcium silicate carbonized product is the ignition loss of the calcium silicate carbonized product at 300° C.-1000° C., and the heating rate is ≤10° C. / min.